Biodiversity of Trichoderma species of healthy and Fusarium wilt-infected banana rhizosphere soils in Tenerife (Canary Islands, Spain) - Correa-Delgado, Raquel; Brito-López, Patricia; Jaizme Vega, María C.; Laich, Federico (Frontiers in Microbiology, 2024)
Banana (Musa acuminata) is the most important crop in the Canary Islands (38.9% of the total cultivated area). The main pathogen affecting this crop is the soil fungal Fusarium oxysporum f. sp. cubense subtropical race 4 (Foc-STR4), for which there is no effective control method under field conditions. Therefore, the use of native biological control agents may be an effective and sustainable alternative. This study aims to: (i) investigate the diversity and distribution of Trichoderma species in the rhizosphere of different banana agroecosystems affected by Foc-STR4 in Tenerife (the island with the greatest bioclimatic diversity and cultivated area), (ii) develop and preserve a culture collection of native Trichoderma species, and (iii) evaluate the influence of soil chemical properties on the Trichoderma community. A total of 131 Trichoderma isolates were obtained from 84 soil samples collected from 14 farms located in different agroecosystems on the northern (cooler and wetter) and southern (warmer and drier) slopes of Tenerife. Ten Trichoderma species, including T. afroharzianum, T. asperellum, T. atrobrunneum, T. gamsii, T. guizhouense, T. hamatum, T. harzianum, T. hirsutum, T. longibrachiatum, and T. virens, and two putative novel species, named T. aff. harzianum and T. aff. hortense, were identified based on the tef1-α sequences. Trichoderma virens (35.89% relative abundance) and T. aff. harzianum (27.48%) were the most abundant and dominant species on both slopes, while other species were observed only on one slope (north or south). Biodiversity indices (Margalef, Shannon, Simpson, and Pielou) showed that species diversity and evenness were highest in the healthy soils of the northern slope. The Spearman analysis showed significant correlations between Trichoderma species and soil chemistry parameters (mainly with phosphorus and soil pH). To the best of our knowledge, six species are reported for the first time in the Canary Islands (T. afroharzianum, T. asperellum, T. atrobrunneum, T. guizhouense, T. hamatum, T. hirsutum) and in the rhizosphere of banana soils (T. afroharzianum, T. atrobrunneum, T. gamsii, T. guizhouense, T. hirsutum, T. virens). This study provides essential information on the diversity/distribution of native Trichoderma species for the benefit of future applications in the control of Foc-STR4.